Proses pemahaman daripada perspektif metakognitif dalam kalangan pelajar universiti - Othman, Yahya; Mustapha, Ghazali; Baki, Roselan; Ahmad, Shamsuddin (Universiti Putra Malaysia Press, 2008)
Comprehending text would be the major aim in a reading process. For students at tertiary levels, the ability to comprehend is normally associated with their field of study. By applying critical and analytical thinking, students would normally have various perspectives about the application of metacognition in reading. Some students face difficulty in developing comprehension while reading text and they also find it difficult to apply specific reading strategy. This study is conducted to examine the perspective of university students about text comprehension using a qualitative research approach. Eight students enrolled in the bachelor in education programme participate in this study. Data was obtained through interviews, document analysis, and classroom observation. The findings indicate that students have various meta-cognition perspectives in interpreting comprehension ability of a text. The difference in perspective is also influenced by the reading strategies used, the level of text difficulty, type of text and students’ perception of the text read.